Idiomatic Expressions Found in Taylor Swift's Song 'All Too Well (10 Minute Version)’ - Kadek Ayu Siwi Patmawati; I Gusti Agung Sri Rwa Jayantini (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research analyzes idiomatic expressions in Taylor Swift’s song "All Too Well (10 Minute Version)." A qualitative approach focused on content analysis of the song's lyrics. The data were collected by transcribing and analyzing the lyrics to identify and classify idiomatic expressions using Makkai's (1972) theory. The analysis revealed a total of 11idiomatic expressions, categorized into Phrasal Verb Idioms (1 idiom), Tournure Idioms (7 idioms), Irreversible Binomial Idioms (1 idiom), and Phrasal Compound Idioms (3 idioms). Tournure Idioms were the most frequently used, highlighting their prominence in conveying the song's themes. This study contributes to the understanding of idiomatic expressions in song lyrics and their role in enhancing lyrical content.